2022
DOI: 10.1007/s42452-022-05186-7
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal monitoring of potentially toxic elements in Lagos harbour water and its health risk implications

Abstract: Continuous discharge of industrial and domestic inputs from various processes into the Lagos lagoon has significantly affected the quality of the aquatic environment, as a result of potentially toxic elements (PTEs) being released into the harbour during anthropogenic activities. This study involved monitoring the concentration and distribution of heavy metals in Lagos harbour during the dry and wet seasons. The PTEs can pose a serious ecological threat to the marine environment as well as human beings when th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…Ihenyen (1991) observed that the part of the harbour where shipping activity was most intensive had low levels of heavy metal pollution, whereas the area around the harbour entrance and the northwest sections, associated with effluent release from industries had medium and high levels of pollution respectively. However, in a recent study, Basheeru et al (2022) investigated the health risk of potentially toxic elements (PTEs) in surface water of the Lagos harbor. The authors found variable amounts of Pb, Cd, Cr, and Ni in the harbour's water, with the greatest quantities found in industrial zones and shipping lanes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ihenyen (1991) observed that the part of the harbour where shipping activity was most intensive had low levels of heavy metal pollution, whereas the area around the harbour entrance and the northwest sections, associated with effluent release from industries had medium and high levels of pollution respectively. However, in a recent study, Basheeru et al (2022) investigated the health risk of potentially toxic elements (PTEs) in surface water of the Lagos harbor. The authors found variable amounts of Pb, Cd, Cr, and Ni in the harbour's water, with the greatest quantities found in industrial zones and shipping lanes.…”
Section: Discussionmentioning
confidence: 99%
“…The potential accumulation of waterborne heavy metals particularly Cadmium (Cd), Iron (Fe), Lead (Pb), Cobalt (Co) and Zinc (Zn) may have potential threat to marine communities and aggravate human health (Bryan and Langston, 1992). It should be noted that previous studies such as Chukwu and Akinyanmi (2018) and Basheeru et al (2022) have survey the impact of pollutants from shipping operations in the past. However, the results of those studies may have been influenced by various other sources such as river runoffs and atmospheric depositions.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, Adeyemi et al [31] and Yahaya et al [20] found non-permissible levels of heavy metals in water samples collected from Ologe Lagoon in Lagos. Bawa-Allah et al [32] and Basheeru et al [10] also reported non-permissible levels as well as carcinogenic and non-carcinogenic health risks of some heavy metals in water samples obtained in the Lagos Lagoon. This consistency suggests that long-term exposure to water from lagoons in Lagos may cause health hazards.…”
Section: Levels and Health Risks Of Heavy Metals In The Water Samplesmentioning
confidence: 96%
“…These activities could potentially pollute the water, yet there is no documented study on the pollution index of the water at the terminal. Recent studies conducted in the Lagos Harbour and Epe sections of the lagoon by Basheeru et al [10] and Yahaya et al [11], respectively, detected non-permissible levels of heavy metals in the lagoon. To protect people's health, it is important to do similar studies at the Ikorodu Lighter Terminal.…”
Section: Introductionmentioning
confidence: 96%